The antiobesity factor WDTC1 suppresses adipogenesis via the CRL4WDTC1 E3 ligase. (9th April 2016) - Groh, Beezly S; Yan, Feng; Smith, Matthew D; Yu, Yanbao; Chen, Xian; Xiong, Yue
Abstract: WDTC1/Adp encodes an evolutionarily conserved suppressor of lipid accumulation. While reduced WDTC1 expression is associated with obesity in mice and humans, its cellular function is unknown. Here, we demonstrate that WDTC1 is a component of a DDB1‐CUL4‐ROC1 (CRL4) E3 ligase. Using 3T3‐L1 cell culture model of adipogenesis, we show that disrupting the interaction between WDTC1 and DDB1 leads to a loss of adipogenic suppression by WDTC1, increased triglyceride accumulation and adipogenic gene expression. We show that the CRL4 WDTC 1 complex promotes histone H2AK119 monoubiquitylation, thus suggesting a role for this complex in transcriptional repression during adipogenesis. Our results identify a biochemical role for WDTC1 and extend the functional range of the CRL4 complex to the suppression of fat accumulation. Synopsis: WDTC1/Adp has demonstrated to possess fat‐suppressive functions in many organisms. This study elucidates the biochemical activity underlying the antiadipogenic function of WDTC1. The antiobesity gene WDTC1 is a component of the CRL4 E3 ligase complex. CRL4 WDTC1 E3 ligase negatively regulates adipogenesis. CRL4 WDTC1 promotes H2AK119 monoubiquitylation. Abstract : WDTC1/Adp has demonstrated to possess fat‐suppressive functions in many organisms. This study elucidates the biochemical activity underlying the antiadipogenic function of WDTC1.